The Effect of Village Fund on Inequality and Inclusive Growth in Indonesia: A District Level Case Study - Putra, Wahyu Pratama; Prasetyia, Ferry (Universitas Syiah Kuala, 2024)
Objective This study tries to find the relationship between Village Fund expenditures and the inequality and growth inclusiveness using data from 434 districts for the time span of seven years from 2015 to 2021.Design/Methodology This study uses quantitative research. The research data comprised the data of Village Fund, Gini Ratio, and Inclusive Growth Index from the Ministry of Finance, Central Bureau of Statistics, and the Ministry of National Development Planning. To investigate the relationship between variables, a dynamic panel data with Generalized Method of Moment (GMM) approach is applied.Results This study revealed the relationship between Village Fund and Inequality and Inclusive Growth. We found that there is no strong relationship between the Village Fund, the first lag of the Village Fund, the second lag of Village Fund and Inequality among specifications. Similar relationships are also shown by the Village Fund, the first lag of Village Fund, the second lag of the Village Fund, and the Inclusive Growth among specifications. In other words, the implementation of Village Fund could not eradicate the inequality problem and could not support inclusion of economic growth in the village level.Research Limitations/Implications The result of this study potentially has a major implication in terms of program delivery effectiveness and the factors that influence the program effectiveness. Furthermore, in this particular research, the major problems with village fund allocation are the equity issue of the allocation scheme and the clarity of the village service responsibilities.Novelty/Originality This study uses a different approach to the panel data, which is a dynamic panel data with GMM approach. This study also uses a more specific scope of the data which is a district (kabupaten/kota) level in Indonesia.